Pemberian - Indrasuari, A.A Istri Diah; Muliarta, I Made; Sundari, Luh Putu Ratna; Sutjana, I Dewa Putu; Tirtayasa, Ketut; Surata, I Wayan (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2021)
The characteristics of nurses' work in the general treatment unit of the North Denpasar Health Center are nursing diagnoses during service hours followed by administrative work, without short breaks. The intervention was carried out in the form of Workplace Stretching Exercise, by giving sweet tea and listening to music after service hours. This study aims to reduce mental burden and fatigue and improve nurses’ performance. The study used treatment by subject design which involved 14 samples. Period 1 was work process without intervention and Period 2 was work process with interventions in the form of giving stretching, sweet tea and music. Mental load was recorded using a NASA-TLX questionnaire, fatigue was recorded with a 30 item exhaustion questionnaire and performance was recorded with a performance questionnaire. Data were analysed using t-paired with a value of ? 0.05 for normally distributed data and Wilcoxon test for data that was not normally distributed. The results showed the mean mental load score was higher in Period I, i.e. the work process without intervention which was 65.14, the mean fatigue score was higher when after working in Period I which was 57.36 and the mean score of performance was higher in Period II which was 3.82. Provision of Workplace Stretching Exercise, sweet tea and listening to music reduced mental burden by 37.05%, reduced fatigue by 33.56% and improved performance by 25.66%. It was concluded that the provision of ergonomics in the form of Workplace Stretching Exercise, sweet tea and listening to music reduced mental burden, fatigue and significantly improved performance of nurses in the general treatment unit at the North Denpasar Health Center.